Akuaponik: Alternatif Kemandirian Masyarakat dalam Pemenuhan Gizi Keluarga - Supriyatin, Supriyatin; Rahayu, Sri; Fitriasih, Fajarani; Arifin, Uswatun Khasanah; Yanuar, Rizki Aditya; Fadillah, Taufik Ismail (Jurnal SOLMA, 2024)
Background: The community lacks information, enthusiasm, and drive about the advantages of veggies and the development of methods for growing them that are simple to implement on little land. There are steps that may be taken to educate the public about vegetable production, which is simple to do in situations when planting space is few. Purpose: The community will get instruction from this program on how to connect aquaponics methods with produce cultivation. Method: partners from the East Jakartan community of Duren Sawit Village. There were fourteen people present. This is a hands-on approach to learning. One method of descriptive analysis is data measurement. A multiple-choice exam was used to gauge the participants' level of knowledge, and a questionnaire was used to gauge their interest, motivation, and satisfaction. Results: demonstrate that, with an average score of 74.64, the participant's comprehension of the training content was rather strong prior to its delivery. Following their participation in the program, participants' average score was 80.00. The average score on the pretest and the average score on the posttest differs significantly, as shown by the 2-tailed sig value of 0.009 <0.005 derived from the t-test findings. 84.5 and 89.3 respectively represent the average interest and motivation scores. The satisfaction level was measured on a scale from 75 to 100%. Conclusion: participant training exercises completing the task is able to grow vegetables on a small plot of land and comprehend their advantages.